The procedure of capacity estimation for P&R car parks located within metropolitan areas - Szarata, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The main purpose of the paper is to estimate P&R demand, which can be useful in estimation of its capacity. The proposed approach is based on the assessment of parking location in terms of connections with public transport system, attractiveness of the location and spatial development of surroundings. Within the analysis, the number of Park and Ride trips was estimated. The proposed approach has been applied to six planned locations of Park and Ride system in Warsaw agglomeration and the analyses were conducted on a simulation model of the whole agglomeration.